3D printed stretchable capacitive sensors for highly sensitive tactile and electrochemical sensing. (8th March 2018) - Li, Kai; Wei, Hong; Liu, Wenguang; Meng, Hong; Zhang, Peixin; Yan, Chaoyi
Abstract: Developments of innovative strategies for the fabrication of stretchable sensors are of crucial importance for their applications in wearable electronic systems. In this work, we report the successful fabrication of stretchable capacitive sensors using a novel 3D printing method for highly sensitive tactile and electrochemical sensing applications. Unlike conventional lithographic or templated methods, the programmable 3D printing technique can fabricate complex device structures in a cost-effective and facile manner. We designed and fabricated stretchable capacitive sensors with interdigital and double-vortex designs and demonstrated their successful applications as tactile and electrochemical sensors. Especially, our stretchable sensors exhibited a detection limit as low as 1 × 10 −6 M for NaCl aqueous solution, which could have significant potential applications when integrated in electronics skins.